The Role of Meaning in Life and Emotional Resilience in Predicting Mental Toughness: A Cross-Sectional Study - Azad, Sedighe; Motaharinia, Setayesh; Alavi Neghad, Sayyed Sayar; Derakhshande , Mansour (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This study aimed to investigate the predictive relationships between mental toughness, meaning in life, and emotional resilience. A cross-sectional design was employed, involving 290 participants recruited through convenience sampling. Data were collected using the Mental Toughness Questionnaire (MTQ48), Meaning in Life Questionnaire (MLQ), and Connor-Davidson Resilience Scale (CD-RISC). Pearson correlation analysis and linear regression analysis were conducted using SPSS version 27 to examine the relationships between the variables. Descriptive statistics revealed mean scores of 3.65 (SD = 0.85) for mental toughness, 4.32 (SD = 0.67) for meaning in life, and 4.10 (SD = 0.74) for emotional resilience. Pearson correlation analysis showed significant positive correlations between mental toughness and meaning in life (r = 0.45, p < 0.001), and between mental toughness and emotional resilience (r = 0.52, p < 0.001). The regression model was significant (F(2, 287) = 77.41, p < 0.001) with an R^2 value of 0.35, indicating that meaning in life and emotional resilience explained 35% of the variance in mental toughness. In the regression analysis, meaning in life (B = 0.28, SE = 0.09, β = 0.25, t = 3.11, p = 0.002) and emotional resilience (B = 0.41, SE = 0.07, β = 0.38, t = 5.86, p < 0.001) were significant predictors of mental toughness. The study demonstrated that both meaning in life and emotional resilience are significant predictors of mental toughness, together explaining a substantial proportion of its variance. These findings highlight the importance of fostering a sense of meaning and enhancing emotional resilience to develop mental toughness, which is crucial for managing stress and adversity.